Early caplacizumab and obinutuzumab enable successful treatment of relapsing thrombotic thrombocytopenic purpura without therapeutic plasma exchange: a case report - Schimpf, Judith; Haller, Patrizia; Zitt, Emanuel (Frontiers in Immunology, 2025)
Thrombotic thrombocytopenic purpura (TTP) is a rare and life-threatening disorder due to a severe acquired or inherited ADAMTS13 deficiency. So far, therapeutic algorithms almost universally include the prompt initiation of therapeutic plasma exchange (TPE). We firstly report a 55-year-old female with a history of relapsing TTP who was managed exclusively with caplacizumab, steroids and the second generation fully humanized anti-CD20 monoclonal antibody obinutuzumab during a relapse without the need of TPE throughout the whole disease course. This case illustrates the safety and effectiveness of a TPE-free TTP management using prompt initiation of caplacizumab and obinutuzumab.